ELECTROCHEMICAL STUDY OF THE REMOVAL OF Cd(II) IONS IN AQUEOUS SOLUTIONS USING ACTIVATED CARBON OBTAINED FROM ORANGE PEEL - La Rosa Toro G, Adolfo (2022)
The use of vegetable waste to obtain activated carbon has been used in recent years for the removal of heavy metal contaminants in water. For this reason, this study presents the obtaining of activated carbon from recycled orange peel (OPAC), synthesized by two activation processes and then thermal treatment, for the removal of cadmium ions, Cd(II), due to its high toxicity. Characterizations by Raman and FT-IR spectroscopy indicated the presence of characteristic functional groups of carbon. The evaluation of the surface area calculated by the BET (Brunauer-Emmett-Teller) method, yielded a specific surface area of 154,96 m2.g-1 and a pore size distribution of 6,70 nm and 12,39 nm calculated by the BJH method (Barrett-Joyner-Halenda). The removal process in different supporting electrolytes was evaluated by the electrochemical method of square wave voltammetry (SWV), obtaining 0,1 mol.L-1 HCl as the optimal electrolyte for removal. In addition, the study of the kinetic process carried out in a time of 6 hours, reached a removal capacity (qe) of Cd(II) of 7,52 g.g-1 and a removal percentage (%R) of 60%. This study establishes that the Cd(II) adsorption process by OPAC follows a pseudo first order model, represented by Log(qmax - qt) = 0,94 - 0,0024t with r2 = 0,9134.